Plantar thermography is useful in the early diagnosis of diabetic neuropathy - Balbinot, Luciane Fachin (2012)
OBJECTIVES: This study evaluated plantar thermography sensitivity and specificity in diagnosing diabetic polyneuropathy using cardiac tests (heart rate variability) as a reference standard because autonomic small fibers are affected first by this disease. METHODS: Seventy-nine individuals between the ages of 19 and 79 years old (28 males) were evaluated and divided into three groups: control (n = 37), pre-diabetics (n = 13) and type 2 diabetics (n = 29). The plantar images were recorded at baseline and then minutes after a provocative maneuver (Cold Stress Test) using an infrared camera that is appropriate for clinical use. Two thermographic variables were studied: the thermal recovery index and the interdigital anisothermal technique. Heart rate variability was measured in a seven-test battery that included three spectral indexes (in the frequency domain) and four Ewing tests (the Valsalva maneuver, the orthostatic test, a deep breathing test, and the orthostatic hypotension test). Other classically recommended tests were applied, including electromyography (EMG), Michigan inventory, and a clinical interview that included a neurological physical examination. RESULTS: Among the diabetic patients, the interdigital anisothermal technique alone performed better than the thermal recovery index alone, with a better sensitivity (81.3%) and specificity (46.2%). For the pre-diabetic patients, the three tests performed equally well. None of the control subjects displayed abnormal interdigital anisothermal readouts or thermal recovery indices, which precluded the sensitivity estimation in this sample of subjects. However, the specificity (70.6%) was higher in this group. CONCLUSION: In this study, plantar thermography, which predominately considers the small and autonomic fibers that are commonly associated with a sub-clinical condition, proved useful in diagnosing diabetic neuropathy early. The interdigital anisothermal test, when used alone, performed best.